(-A --> -A) --> A

(A --> A) --> (B <--> -A)

(-A --> -A) --> (A --> A) --> (B <--> -A)

## Double Negatives and Double Positives Self-Referentially Alternate

### Re: Double Negatives and Double Positives Self-Referentially Alternate

(-A --> -A) --> A

The not cat is the not cat therefore cat. This necessitates cat as existing where the negation of one phenomena necessitates a non negated state as existing.

(A -> A) --> (B <--> -A)

The cat is the cat therefore x type of cat exists if and only of a not cat exists. This necessitates x type of cat existing considering one being progresses to a type of that being through a regression with x being what is not a cat. For example "bengal" or "wild" is a phenomena which is not limited to cat thus is a phenomena which is not cat is produced through the regression.

(-A --> A) --> (B <--> -A)

The not cat necessitates cat as existing therefore x type of cat exists if and only if not cat exists. The cat as existing necessitates a type of cat as existing. This type of cat existing necessitates a phenomena, as the type, existing which is not cat.

The not cat is the not cat therefore cat. This necessitates cat as existing where the negation of one phenomena necessitates a non negated state as existing.

(A -> A) --> (B <--> -A)

The cat is the cat therefore x type of cat exists if and only of a not cat exists. This necessitates x type of cat existing considering one being progresses to a type of that being through a regression with x being what is not a cat. For example "bengal" or "wild" is a phenomena which is not limited to cat thus is a phenomena which is not cat is produced through the regression.

(-A --> A) --> (B <--> -A)

The not cat necessitates cat as existing therefore x type of cat exists if and only if not cat exists. The cat as existing necessitates a type of cat as existing. This type of cat existing necessitates a phenomena, as the type, existing which is not cat.